Kinerja Environmental, Social, dan Governance (ESG) dan Penghindaran Pajak: Peran Moderasi Kualitas Institusi di ASEAN - Rosmaryam Rosmaryam; Mursalim Mursalim; Juliyanti Sidik Tjan (Politeknik Ganesha Medan, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance on corporate tax avoidance and to analyze the moderating role of institutional quality in the context of non-financial firms across Southeast Asia (ASEAN), specifically Indonesia, the Philippines, Thailand, and Vietnam during the period 2017–2023. This research employs a quantitative explanatory approach using an unbalanced panel dataset comprising 1,344 firm-year observations. Tax avoidance is proxied by the Effective Tax Rate (ETR) as the primary measure and Book–Tax Difference (BTD) as a robustness check. ESG scores are obtained from the Bloomberg database, while institutional quality is measured using Regulatory Quality and Control of Corruption indicators from the World Governance Indicators. The analysis is conducted using panel data regression with a Random Effect Model (REM) and moderation interaction testing, processed through STATA. The results indicate that ESG performance has a negative and statistically significant effect on tax avoidance, suggesting that firms with stronger sustainability commitments tend to exhibit higher fiscal compliance. Furthermore, institutional quality strengthens this negative relationship, implying that ESG is more effective in constraining tax avoidance practices in countries with stronger institutional environments. Robustness tests using BTD and additional country-level analyses confirm the consistency of the findings, although the magnitude of the effect varies across countries. This study is limited by its reliance on quantitative proxies that may not fully capture the substantive implementation of ESG practices. Theoretically, the findings reinforce the integration of Agency Theory, Legitimacy Theory, and Institutional Theory in explaining corporate tax behavior. Practically, the results highlight the importance of strengthening institutional quality and promoting credible ESG implementation to enhance corporate tax compliance in ASEAN. Future research may explore the individual dimensions of ESG and address potential endogeneity using advanced econometric techniques